Factors affecting the efficacy of the Australian indigenous business exemption. Issue 1 (4th March 2019) - Storey, Matthew
Abstract : Purpose: This paper aims to describe a qualitative research project that investigated factors leading to the very low use of the Australian Commonwealth Government's indigenous business exemption (IBE), particularly from 2011 to 2015. Design/methodology/approach: The project involved interviews with 12 selected stakeholders from Indigenous firms, procuring agencies and policy designers, which took place in 2016. Findings: Analysis of the interviews suggested that poor use of the IBE was primarily attributed to risk aversion inside government and limited communication of the existence of the policy outside government. Originality/value: A range of other factors and methods of overcoming these problems are also identified; principal amongst these is the need for procuring agencies to engage with Indigenous suppliers in a coordinated and deliberate fashion.